2002
DOI: 10.1577/1548-8675(2002)022<1007:eowfaf>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Walleye Fry and Fingerling Stocking in Rathbun Lake, Iowa, 1990–1999

Abstract: I evaluated the performance of walleyes Stizostedion vitreum in Rathbun Lake, Iowa, by comparing stockings of fry, intensively reared fingerlings, and extensively reared fingerlings (fall and spring) during 1984–1999. The management goal was to triple the biomass of walleye adults (>17.5 in). Fry were stocked at 2,000/acre (1984–1995) and 3,000/acre (1996–1999), extensively reared fingerlings were stocked at 10/acre (1984–1990), and intensively reared fingerlings were stocked at 5/acre (1985–1999). Spring‐ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…; Rypel et al. ), whereas Walleye cannot naturally reproduce or their recruitment is limited in other locations (Mitzner ; Reed and Staples ; Koch et al. ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…; Rypel et al. ), whereas Walleye cannot naturally reproduce or their recruitment is limited in other locations (Mitzner ; Reed and Staples ; Koch et al. ).…”
mentioning
confidence: 99%
“…Walleye stocking programs often rely on stocking large numbers of fry (~10 mm TL); this strategy can be successful in some instances (e.g., Logsdon et al. ) but is more often unsuccessful in many situations (Laarman ; Mitzner ). Large fingerling Walleye (>200 mm TL) are also commonly stocked (Kerr ; Summerfelt et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…). Adult Walleye densities in Rathbun Lake and other locations throughout the Midwestern USA tend to be low due to limited or no natural recruitment, and populations are subsequently maintained by stocking (Willis and Stephen ; Mitzner ). Thus, even low adult emigration rates from reservoirs may substantially reduce population densities.…”
mentioning
confidence: 99%
“…For example, in a review of walleye stocking case histories, Laarman (1978) reported that only one-third of all supplemental stockings were effective, and Ellison and Franzin (1992) reported success rates ranging from 32% to 50%. Although numerous studies have reported successful stocking efforts in the Midwestern United States (e.g., Lucchesi 2002;Mitzner 2002), few studies have examined the success of walleye stocking programs in the Southeast, despite the long practice of stocking in this region of North America (Hackney and Holbrook 1978).…”
mentioning
confidence: 99%